Investasi, Inflasi dan Konsumsi: Pengaruhnya terhadap Pertumbuhan Ekonomi di Kalimantan Selatan - Saibana, Ikhwan; Noval, Muhammad; Aminah, Siti; Nafila, Haifa; Rosadi, Mila (Ecoplan, 2024)
Economic growth is used as an important indicator in measuring the success or failure of economic development. A growing economy indicates economic development that each economic sector has achieved within a certain period. This research aims to determine the economic growth in South Kalimantan in terms of investment, inflation, and consumption. The research method used in this research is multiple linear regression analysis using hypothesis testing, namely the t-test and F-test, based on data obtained in time-series form with an observation period from 2006 to 2021. Secondary data from published data from the Agency The Statistics Center (BPS) of South Kalimantan Province forms investment performance values, inflation, and consumption as independent variables. Meanwhile, the dependent variable is economic growth. The research results prove that economic growth is partially influenced by inflation and consumption; high unstable inflation will hurt economic growth, and high consumption will encourage economic performance. Meanwhile, investment does not affect the economic growth of South Kalimantan because the amount of investment depends on the efficiency and accuracy of policy targets, the availability of adequate human resources and infrastructure, and a stable political situation. Investment, inflation, and consumption variables influence the simultaneous test of economic growth in South Kalimantan.